Medicinal plants for the treatment of snakebites among the rural populations of Indian subcontinent: An indication from the traditional use To pharmacological confirmation - Ramaswamy, Malathi; Duraikannu, Sivakumar; Solaimuthu, Chandrasekar (Journal of Drug Delivery and Therapeutics, 2018)
Snakebite is one of the important medical problems that affect the public health due to their high morbimortality. Most of the snake venoms produce intense lethal effects, which could lead to impermanent or permanent disability or in often death to the victims. The accessible specific treatment was using the antivenom serum separated from envenomed animals, whose efficiency is reduced against these lethal actions but it has a serious side effects. In this circumstance, this review aimed to provide an updated overview of herbal plants used popularly as antiophidic agents and discuss the main species with pharmacological studies supporting the uses, with prominence on plants inhibiting the lethal effects of snake envenomation amongst the rural tribal peoples of India. There are several reports of the accepted use of herbal plants against snakebites worldwide. In recent years, many studies have been published to giving pharmacological confirmation of benefits of several vegetal species against local effects induced by a broad range of snake venoms, including inhibitory potential against hyaluronidase, phospholipase, proteolytic, hemorrhagic, myotoxic, and edematogenic activities. In India, a variety of herbal plants are used to cure against the snakebites and other poisonous bites, used either in alone or in combination with other herbal agents. The present study was designed to formulate an attempt to bring together information on medicinal plants that are grown and used for snakebite treatment in India. From a variety of literature sources, data have been compiled with prominence on the plants, family, parts used, etc., depending on the availability of information.